Will sacubitril-valsartan diminish the clinical utility of B-type natriuretic peptide testing in acute cardiac care? - Mair, Johannes; Giannitsis, Evangelos (European heart journal - acute cardiovascular care, 2017)
Since the approval of sacubitril-valsartan for the treatment of chronic heart failure with reduced ejection fraction, a commonly raised suspicion is that a wider clinical use of this new drug may diminish the clinical utility of B-type natriuretic peptide testing as sacubitril may interfere with B-type natriuretic peptide clearance. In this education paper we critically assess this hypothesis based on the pathophysiology of the natriuretic peptide system and the limited published data on the effects of neprilysin inhibition on natriuretic peptide plasma concentrations in humans. As the main clinical application of B-type natriuretic peptide testing in acute cardiac care is and will be the rapid rule-out of suspected acute heart failure there is no significant impairment to be expected for B-type natriuretic peptide testing in the acute setting. However, monitoring of chronic heart failure patients on sacubitril-valsartan treatment with B-type natriuretic peptide testing may be impaired. In contrast to N-terminal-proBNP, the current concept that the lower the B-type natriuretic peptide result in chronic heart failure patients, the better the prognosis during treatment monitoring, may no longer be true.
Article first published online: January 12, 2016
Gesehen am 22.08.2018